2010
DOI: 10.3390/d2071026
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of the Archaeal Community in an Amazonian Wetland Soil and Culture-Dependent Isolation of Methanogenic Archaea

Abstract: Tropical wetlands are the major natural source of methane released into the atmosphere, producing about 60% of all natural emissions. The great wetland areas of the Amazon basin are the largest source of methane in this region, contributing an estimated 5% of the total emissions from the world's flooded areas. However, despite the important role that methanogenic archaea play in these environments, there have been few studies on the composition of their archaeal communities. In this survey, four 16S rRNA archa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 67 publications
3
13
0
2
Order By: Relevance
“…This variation of nutrients may explain the significant difference between 10 and 40 cm depths. Along with our findings, several studies have also demonstrated that the microbial structure responds to different depths in soils [39][40][41][42]. Arrows indicate correlation between the chemical parameters and sample community structure.…”
Section: Resultssupporting
confidence: 76%
“…This variation of nutrients may explain the significant difference between 10 and 40 cm depths. Along with our findings, several studies have also demonstrated that the microbial structure responds to different depths in soils [39][40][41][42]. Arrows indicate correlation between the chemical parameters and sample community structure.…”
Section: Resultssupporting
confidence: 76%
“…In Eastern Amazon wetland soils Archaeal community was characterized by 16S rRNA gene libraries and by isolation of methanogenic Archaea (Pazinato et al, 2010). Archaeal diversity decreased with depth and the most of sequences belonging to Crenarchaeota, Methanosarcina and Metahnobacteriam genera were isolated from the sites.…”
Section: Main Aim Of Thementioning
confidence: 99%
“…In this context, Brazil has been slowing down deforestation by trying to make better use of already cleared land (Tollefson, 2010). However, the establishment of policies for the sustainable use of land in the Amazon region requires considering not only the diversity of flora and fauna but also the aspects of microbial ecology and biogeochemistry represented in this region as well (Piccolo et al, 1994;Borneman & Triplett, 1997;Moraes et al, 2002;Cenciani et al, 2009;Chaves et al, 2009;Jesus et al, 2009;O'Neill et al, 2009;Pazinato et al, 2010).…”
Section: Introductionmentioning
confidence: 99%